Determinants of Capital Structure: An Expanded Assessment - Fukui, Toshinori; Mitton, Todd; Schonlau, Robert (Journal of Financial and Quantitative Analysis, 2023)
Using a standardized methodology, we empirically evaluate 55 proposed determinants of capital structure in terms of statistical significance, economic significance, and identification. We find that robust and economically important determinants of debt ratios are relatively few in number. Nevertheless, because each determinant relates to one of five market imperfections—taxes, distress costs, information asymmetry, agency costs, or supply frictions—we draw conclusions from the evidence as a whole regarding the explanatory power of different capital structure theories. We find greater support for pecking order theory and supply-related theories, with less support for traditional tradeoff theory and agency theory.